(untitled) (Comprehensive Journal of Science, 2025)
This study aims to explore and develop an integrated theoretical and applied framework to enhance the effectiveness of banking supervision in the context of accelerated digital transformation. The study adopts a proactive vision that treats technology not as an external factor, but as a key moderator variable that reshapes the relationship between the three control mechanisms (Board of Directors, Internal Audit, External Audit) and risk management effectiveness. Research Problem: The problem lies in the widening gap between rapid technological development and the slow updating of traditional supervisory systems, as revealed by successive financial crises (2008, COVID-19 pandemic), particularly in developing environments like Libya where challenges are exacerbated by weak infrastructure and security conditions. Main Objectives: The study seeks to: measure the impact of activating digitally-enhanced control mechanisms on risk management efficiency; analyze the ability of supervisory systems to adapt to emerging technologies; enhance regulatory compliance by improving the quality of digital financial disclosure; and formulate practical strategies to achieve balance between technological reliance and human resource development. Findings and Recommendations: The study concluded there is a positive relationship between digital transformation maturity and supervisory effectiveness, while emphasizing the necessity of a hybrid model that integrates human and artificial intelligence. It provided practical recommendations at multiple levels: strategic for boards of directors, developmental for audit departments, regulatory for supervisory authorities, and academic for research centers. Philosophical Conclusion: The study affirms that technology is a means to enhance transparency, efficiency, and security, not an end in itself. The future of financial stability depends on the ability to integrate technological innovation within sound governance frameworks, where human wisdom remains the ultimate guide to digital power, in a complementary relationship aimed at building institutional immunity capable of confronting the complexities of the digital age.